Exposure of Endocrine Disrupting Chemicals: A Growing Public Health Concern in Faisalabad, Pakistan - Qader, Abdul; Hayat, Muhammad Khawar; Khaliq, Rabia (Health Dynamics, 2025)
Endocrine disrupting chemicals (EDCs) are gradually documented as public health hazards in agricultural and industrial centers of Pakistan. Faisalabad, is known as a major pivot point for intensive farming and textile manufacturing, presents multiple sources of exposure including industrial effluents, pesticide residues, and consumer products. However, the exposure of EDCs at population level leftovers under-addressed. The data documented in this study was collected from recent environmental and biomonitoring studies conducted in Punjab, Pakistan. For this purpose, we reviewed literature on EDCs concentrations in food items, groundwater, and biological samples, with special focus on bisphenol A (BPA), organochlorine pesticides, and phthalate metabolites. In conclusion, Faisalabad’s polluted groundwater supply, convergence of dyeing industry effluents, and pesticide-intensive agriculture create a significant risk of low dose, chronic exposure to various EDCs which are associated with metabolic disorders, warranting urgent public health interventions.